The Histamine H3 Receptor Antagonist DL77 Ameliorates MK801-Induced Memory Deficits in Rats - Eissa, Nermin; Khan, Nadia; Ojha, Shreesh K.; Łazewska, Dorota; Kieć-Kononowicz, Katarzyna; Sadek, Bassem (Frontiers in Neuroscience, 2018)
The role of Histamine H3 receptors (H3Rs) in memory, and the prospective of H3R antagonists in pharmacological control of neurodegenerative disorders, e.g. Alzheimer disease (AD) is well accepted. For that reason, the procognitive eﬀects of the H3R antagonist DL77 on cognitive impairments induced with MK801 were tested in an inhibitory passive avoidance paradigm (PAP) and novel object recognition (NOR) task in adult male rats, using donepezil (DOZ) as a standard drug. Acute systemic pretreatment with DL77 (2.5, 5, and 10 mg/kg, i.p.) significantly ameliorated memory deficits induced with MK801 in PAP (all P values <0.05, n=7). The ameliorative effect of most promising dose of DL77 (5 mg/kg, i.p.) was reversed when rats were co-injected with the H3R agonist R-(α)-methylhistamine (RAMH, 10 mg/kg, i.p.) (p=0.701 for MK801-amnesic group vs. MK801+DL77+RAMH group, n=6). In the NOR paradigm, DL77 (5 mg/kg, i.p.) counteracted long-term memory (LTM) deficits induced with MK801 (P<0.05, n=6-8), and the DL77-provided effect was similar to that of DOZ (p= 0.788, n=6-8), and was reversed when rats were co-injected with RAMH (10 mg/kg, i.p.) (p= 0.877, n=6, as compared to the (MK801)-amnesic group). However, DL77(5 mg/kg, i.p.) did not alter short-term memory (STM) impairment in NOR test (p= 0.772, n=6-8, as compared to (MK801)-amnesic group). Moreover, DL77 (5 mg/kg) failed to modify anxiety and locomotor behaviors of animals innate to elevated-plus maze (EPM) (p=0.67 for percentage of time spent exploring the open arms, p=0.52 for number of entries into the open arms, p=0.76 for percentage of entries into the open arms, and p=0.73 number of closed arm entries as compared to saline-treated groups, all n=6), demonstrating that the procognitive effects observed in PAP or NOR tests were unconnected to alterations in emotions or in natural locomotion of tested animals. These results signify the potential involvement of H3Rs in modulating neurotransmitters related to neurodegenerative disorders, e.g. AD.